825 views
5 votes
-4 3------ = ------- x+2 x+4X=

User Q Studio
by
5.2k points

1 Answer

1 vote

Answer:

The equation is given below as


-(4)/(x+2)=(3)/(x+4)

Step 1:

Cross multiply


\begin{gathered} -(4)/(x+2)=(3)/(x+4) \\ -4(x+4)=3(x+2) \\ -4x-16=3x+6 \end{gathered}

Step 2:

Collect similar terms


\begin{gathered} -4x-16=3x+6 \\ -4x-3x=6+16 \\ -7x=22 \\ divide\text{ both sides by -7} \\ (-7x)/(-7)=(22)/(-7) \\ x=-(22)/(7) \end{gathered}

Hence,

The value of x is


\Rightarrow x=-(22)/(7)

User Fazle Rabbi
by
4.8k points